2020
DOI: 10.3920/jaan2020.0009
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with sodium humate improves egg quality and immune function of laying hens

Abstract: The aim of this study was to evaluate the influence of the dietary addition of sodium humate (HAS) on performance and immune response of laying hens during peak lay, over an eight-week period. Laying hens, aged 24 weeks old, were randomly allotted to four dietary treatments: a basal control diet or the basal diet supplemented with 0.1, 0.3 or 0.5% HAS. Each treatment had six replicates with 15 layers per replicate. Egg production, egg quality, serum antioxidant parameters and immunity indexes were measured. HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
2
8
1
Order By: Relevance
“…Dietary supplementation with HS additives had a significant effect on the laying rate, daily egg mass, egg weight, and feed conversion, which indicate the ability of HS to stabilize the intestinal microbiota, thus ensuring improved nutrient utilization in feed [38,39]. These findings are consistent with our results.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Dietary supplementation with HS additives had a significant effect on the laying rate, daily egg mass, egg weight, and feed conversion, which indicate the ability of HS to stabilize the intestinal microbiota, thus ensuring improved nutrient utilization in feed [38,39]. These findings are consistent with our results.…”
Section: Discussionsupporting
confidence: 89%
“…The increased percentage of the IgM+ lymphocyte subpopulation is consistent with the finding of increased gene expression for IgA in the gut. Zhang et al [38] (2020) also noted significantly elevated serum IgM as well as IgG levels after the administration of 0.1 and 0.5% HS to laying hens, which confirms the activation of B cells. Similarly, Salah et al [53] reported an increase in the serum gamma globulin fraction containing most of immunoglobulins after 5 days of humic acid application to broiler chickens.…”
Section: Discussionmentioning
confidence: 88%
“…For example, elevated lymphoid tissue distribution and density in the bursa of Fabricius and thyme [25] increased concentration of antibodies against infectious bursal disease [69], avian influenza [70], and Newcastle disease virus (NDV) [71,72], and greater lymphocytes and leukocytes counts, globulins (α, β, and γ), phagocytosis, and phagocytic index have been found in HS-added broilers [73]. In laying hens, supplementation HS significantly increased the serum IgG and IgM level [74].…”
Section: Immune Response and Inflammationmentioning
confidence: 99%
“…In laying hens and partridges supplemented with HS, benefits in feed intake, egg production, egg weight, and feed conversion ratio have been observed [118-120, 130, 147]. Improved Haugh unit values and egg yolk color in HS-added laying hens [74] and increased albumen height, albumen index, and Haugh units of the egg in partridge [148] were observed. A strong tendency of lower mortality have been reported in HS-added broilers [25, 67,77] and Japanese quails [27].…”
Section: Productive Response In Animals Supplemented With Humic Subst...mentioning
confidence: 99%
“…Humates (humic substances) are the salt forms of humic acid that originated from microbial decomposition of decayed plant substances, with Na+, K+, Ca 2 +, Fe 2 + and Al 3 + as exchange sites instead of hydrogen (Zhang et al, 2020). Humates is a bioactive compound that consists of humic acid, humus, fulvic acid, ulmic acid and other microelements that exhibit potent anti‐inflammatory, antioxidant, antitoxic, antiviral and immunostimulatory (Arafat et al, 2015; Vaskova et al, 2018).…”
Section: Introductionmentioning
confidence: 99%